2015
DOI: 10.1002/2014ja020963
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy radiation belt electrons from CRAND

Abstract: A calculation of the inner radiation belt electron source from cosmic ray albedo neutron decay (CRAND) is described. High-energy electrons are included by Lorentz-transforming the decay spectrum from the neutron rest frame to the Earth's rest frame and combining with the known high-energy albedo neutron energy spectrum. Balancing the electron source with energy loss to atmospheric neutral atoms and plasma, and with a decay lifetime representative of plasma wave scattering, then provides an estimate of trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Since neutron decay is well understood, its known properties enable evaluation of its contribution. In the neutron rest frame, electrons produced by neutron decay have a beta decay spectrum: ψ()E=normalCE()E+2mec20.25em()E+mec2QE2 where E is electron kinetic energy, Q is the maximum available energy for electrons due to the mass difference ( Q = m n c 2 − m p c 2 − m e c 2 =782 keV), and C is a constant ( C = 17.57 MeV −5 when ∫Ψd E = 1; Selesnick, ). Albedo neutrons below 1 eV have been determined to be responsible for the majority of the energetic electrons of interest (Hess et al, ; Lenchek et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since neutron decay is well understood, its known properties enable evaluation of its contribution. In the neutron rest frame, electrons produced by neutron decay have a beta decay spectrum: ψ()E=normalCE()E+2mec20.25em()E+mec2QE2 where E is electron kinetic energy, Q is the maximum available energy for electrons due to the mass difference ( Q = m n c 2 − m p c 2 − m e c 2 =782 keV), and C is a constant ( C = 17.57 MeV −5 when ∫Ψd E = 1; Selesnick, ). Albedo neutrons below 1 eV have been determined to be responsible for the majority of the energetic electrons of interest (Hess et al, ; Lenchek et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Albedo neutrons below 1 eV have been determined to be responsible for the majority of the energetic electrons of interest (Hess et al, ; Lenchek et al, ). Therefore, we need only to consider neutrons at rest (also discussed in Hess et al, , and Selesnick, ). We can calculate the fluxes of the CRAND‐produced electrons at different energies with lifetime τ e (Li et al, ): J()E=nτnormaleτnv()EnormalΨ()E4π where J is the electron flux, n is the neutron density, τ n is the neutron lifetime, and v is the electron velocity.…”
Section: Methodsmentioning
confidence: 99%
“…Modern physical models of the electron radiation belts allow for radial diffusion, pitch angle scattering, and energy diffusion, where the latter is usually described as momentum diffusion [ Albert et al , ; Xiao et al , ; Su et al , ; Subbotin and Shprits , ; Tu et al , ; Glauert et al , ]. A typical expression for the gyrobounce drift phase‐averaged PSD ( f ) is ft=L2|LM,KDLLL2|fLM,K+1p2|px,Lp2Dpp|fpx,L+p2Dpx|fxp,L+1xTy|xp,LxTyDxx|fxp,L+xTyDxp|fpx,L+S where x is the cosine of the equatorial pitch angle, T ( y ) is a scale factor related to the particle's bounce period, the D s represent diffusion processes, and S represents a source, namely, cosmic ray albedo neutron decay (CRAND) [see, e.g., Selesnick , , and references therein].…”
Section: Analysis Approachmentioning
confidence: 99%
“…They also showed that there were essentially no (or very few) E > 1 MeV electrons present, at least in the early Van Allen Probes mission time frame. Selesnick (2015) showed that the neutron albedo generated electron fluxes are too low to account for the observed E < 1 MeV inner zone electrons, indicating that a different source was responsible for the inner zone electron fluxes. However, his calculations also indicated that the process could generate multi-MeV electrons at low flux levels, below the upper limits set by the Van Allen Probe measurements.…”
Section: Inner Zone Electronsmentioning
confidence: 98%